A new hemophilia carrier nomenclature to define hemophilia in women and girls: Communication from the SSC of the ISTH. (29th July 2021) - van Galen, Karin P. M.; d'Oiron, Roseline; James, Paula; Abdul‐Kadir, Rezan; Kouides, Peter A.; Kulkarni, Roshni; Mahlangu, Johnny N.; Othman, Maha; Peyvandi, Flora; Rotellini, Dawn; Winikoff, Rochelle; Sidonio, Robert F.
Abstract: Hemophilia A and B predominantly attracts clinical attention in males due to X‐linked inheritance, introducing a bias toward female carriers to be asymptomatic. This common misconception is contradicted by an increasing body of evidence with consistent reporting on an increased bleeding tendency in hemophilia carriers (HCs), including those with normal factor VIII/IX (FVIII/IX) levels. The term HC can hamper diagnosis, clinical care, and research. Therefore, a new nomenclature has been defined based on an open iterative process involving hemophilia experts, patients, and the International Society on Thrombosis and Haemostasis (ISTH) community. The resulting nomenclature accounts for personal bleeding history and baseline plasma FVIII/IX level. It distinguishes five clinically relevant HC categories: women/girls with mild, moderate, or severe hemophilia (FVIII/IX >0.05 and <0.40 IU/ml, 0.01–0.05 IU/ml, and <0.01 IU/ml, respectively), symptomatic and asymptomatic HC (FVIII/IX ≥0.40 IU/ml with and without a bleeding phenotype, respectively). This new nomenclature is aimed at improving diagnosis and management and applying uniform terminologies for clinical research.